Post-Activation Performance Enhancement and Motor Imagery Are Efficient to Emphasize the Effects of a Standardized Warm-Up on Sprint-Running Performances - Valentin Rumeau; Sidney Grospretre; Nicolas Babault (MDPI AG, 2023)
Warm-up routines include various tasks focused on the peripheral contractile properties and nervous motor command. This present study was aimed at investigating the acute effects of different warm-up routines, emphasizing either peripheral (post-activation performance enhancement, PAPE) or central (motor imagery, MI) contributions on sport-specific tasks. Eleven young female athletes took part in this cross-over, randomized, controlled trial. They underwent three experimental sessions composed of a standardized warm-up followed by 10 min of (1) rest (CONTROL), (2) maximal concentric leg press (PAPE), or (3) mental repetitions of sprint tasks (MI). Post-tests consisted of reaction time, arrowhead agility test, 20 m sprint, repeated sprint ability, and NASA-TLX fatigue questionnaire. PAPE and MI significantly enhanced the arrowhead agility test (p < 0.001 and p = 0.012, respectively) and repeated sprint ability (p = 0.002 and p = 0.035, respectively) compared to CONTROL, without any difference between PAPE and MI. The 20 m sprint time was better after PAPE as compared to MI (p = 0.005) and CONTROL (p < 0.001), without any difference between MI and CONTROL. Reaction time and the NASA-TLX questionnaire were not affected by the warm-up modalities (p > 0.05). PAPE was the most efficient to optimize warm-up due to its greater peripheral contribution that would improve muscle contractility. MI specifically improved the imagined tasks mostly by central contribution.